Union Budget 2018: reforms in Indian Agriculture - Kumar, Shiv; Chahal, V. P.; Jhajharia, Abimanyu (Indian Farming, 2018)
The Indian farmer faces moremarketing problems than productionof the crops. Middlemen are the baneof Indian agriculture.The informationneeds to be disseminated tostakeholders rigorously at regularperiod to take decisions for sale ofthe produce. The staff of the linedepartment be delegated the job oftying up farmer produce withappropriate regional markets and theProcessing Industry for the best pricerealization. Cultivation of high valueagriculture/ crops in clusters bringadvantages of scales of operations andcan spur establishment of entire chainfrom production to marketing,besides giving recognition to thedistricts for specific crops. A farm tofork approach entails several activitieswhich fall in jurisdiction of severalministries that generatesimpediments and risks in agriculturalmanagement. Budget will consolidategains with focus on strengtheningagriculture economy and ensurebenefits reach eligible beneficiaries.The intent of government onimplementation of a series offundamental structure reforms inagriculture is going to overcome theagrarian crisis to an extent. However,the magnitude of benefits of reformswill become evident with time only.